1989
DOI: 10.1051/parasite/1989642134
|View full text |Cite
|
Sign up to set email alerts
|

Species of the genusElaphostrongylusparasite of Swedish cervidae. A description ofE. alcesn. sp.

Abstract: SUMMARY. A description of Elaphostrongylus alces n. sp., a parasite of moose (Alces alces L.), is given. The main features differing E. alces n. sp. from the other two investigated species are the bottle shaped oesophagus and the oval bursa, which is about 150 µm x 200 µm.E. rangiferi Mitskevith, 1960, a parasite of reindeer (Rangifer tarandus tarandus L.) and E. cervi Cameron, 1931, a parasite of red deer (Cervus elaphus L.) have both a club shaped or cylindrical oesophagus and a circular bursa. The bursa of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
2
14
0
1
Order By: Relevance
“…The genital bursa of Elaphostrongylus sp. from moose, in accordance with the description of E.alces by Steen et al (1989) showed characteristics differing from those found in Elaphostrongylus spp. from reindeer and red deer respectively.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The genital bursa of Elaphostrongylus sp. from moose, in accordance with the description of E.alces by Steen et al (1989) showed characteristics differing from those found in Elaphostrongylus spp. from reindeer and red deer respectively.…”
supporting
confidence: 90%
“…from red deer, reindeer, and moose strengthens earlier descriptions based on light microscopy of E.cervi by Cameron (1931), E.rangiferi by Mitskevich (1960) and E.alces by Steen et al (1989).…”
Section: Elaphostrongylussupporting
confidence: 52%
See 2 more Smart Citations
“…Elaphostrongylus alces Stéen, Chabaud, and Rehbinder, 1989, a recently described species of neurotropic nematode, occurs in moose (Alces alces) of Sweden (Stéen et al 1989) and Norway (Gibbons et al 1991). Adult worms are found in the epidural space of the spinal canal and beneath the fascia of muscles of the chest and limbs.…”
Section: Introductionmentioning
confidence: 99%